Novel Triazolopyrimidine‐Derived Cannabinoid Receptor 2 Agonists as Potential Treatment for Inflammatory Kidney Diseases. Issue 2 (21st July 2015) - Nettekoven, Matthias; Adam, Jean‐Michel; Bendels, Stefanie; Bissantz, Catarina; Fingerle, Jürgen; Grether, Uwe; Grüner, Sabine; Guba, Wolfgang; Kimbara, Atsushi; Ottaviani, Giorgio; Püllmann, Bernd; Rogers‐Evans, Mark; et al.
Abstract: The cannabinoid receptor 2 (CB2) system is described to modulate various pathological conditions, including inflammation and fibrosis. A series of new heterocyclic small‐molecule CB2 receptor agonists were identified from a high‐throughput screen. Lead optimization gave access to novel, highly potent, and selective (over CB1) triazolopyrimidine derivatives. A preliminary structure–activity relationship was established, and physicochemical properties in this compound class were significantly improved toward better solubility, lipophilicity, and microsomal stability. An optimized triazolopyrimidine derivative, (3 S )‐1‐[5‐ tert ‐butyl‐3‐[(1‐cyclopropyltetrazol‐5‐yl)methyl]triazolo[4, 5‐ d ]pyrimidin‐7‐yl]pyrrolidin‐3‐ol (39 ), was tested in a kidney ischemia–reperfusion model, in which it showed efficacy at a dose of 10 mg kg −1 (p.o.). A significant depletion of the three measured kidney markers indicated a protective role of CB2 receptor activation toward inflammatory kidney damage. Compound39 was also protective in a model of renal fibrosis. Oral treatment with39 at 3 mg kg −1 per day significantly decreased the amount of fibrosis by ∼40 % which was induced by unilateral ureter obstruction. Abstract : Kidney protection : A series of small‐molecule CB2 receptor agonists was identified in a high‐throughput screen. Lead optimization work gave access to novel triazolopyrimidine derivatives, highly potent on CB2 and selective over CB1. Optimized compound39 was efficacious in an in vivo model for kidney ischemia–reperfusion and in an in vivo model of renal fibrosis (unilateral ureter obstruction) upon p.o. administration.